Hybrid algorithms, techniques and implementations of fuzzy logic - Stanimirović, Ivan (AOakville, ON, Canada : Arcler Press, 2019)
Studies various aspects of Fuzzy logic including an extensive overview of hybrid algorithms, techniques and implementations. It includes definitions of evolutionary computation and fuzzy systems, ideologies and strategies. This book provides the reader with insights into the development of its knowledge, so as to understand the applications and implementations of fuzzy logic using hybrid algorithms.
10.7. Fuzzy Inference Model To Assess The Reliability of Digital SourcesChapter 11 Final Considerations and Conclusions; 11.1. Possible Applications; 11.2. Conclusions.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Fuzzy logic; Fuzzy algorithms; Logique floue; Algorithmes flous; Fuzzy algorithms; Fuzzy logic